2021
DOI: 10.1038/s41598-021-83203-2
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 genomic surveillance in Rondônia, Brazilian Western Amazon

Abstract: SARS-CoV-2 has spread rapidly around the world, with Brazil currently considered an epicenter of the pandemic. The Northern region has the second highest incidence coefficient, as well as the third highest mortality rate in the country. This study aimed to investigate information about the evolutionary history of epidemic spread and genetic aspects of strains isolated on the Western Amazon, in the State of Rondônia, Brazil. It was possible to detect a total of 22 mutations. Some of these alterations may possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
(59 reference statements)
1
8
0
Order By: Relevance
“…Genome sequencing is an essential step to understand lineage dispersion and to detect mutations. The first viral genomes sequenced available in GISAID from Ceará were classified as B.1 ( Candido et al, 2020 ), and similar results have been reported for other Brazilian states ( Botelho-Souza et al, 2021 ; dos Santos et al, 2021 ). Lineage B.1 was predominant worldwide, especially in Europe, and emerged around January 2020 ( Rambaut et al, 2020 ), contributing to the early viral epidemic dynamics in Brazil ( Candido et al, 2020 ).…”
Section: Discussionsupporting
confidence: 74%
“…Genome sequencing is an essential step to understand lineage dispersion and to detect mutations. The first viral genomes sequenced available in GISAID from Ceará were classified as B.1 ( Candido et al, 2020 ), and similar results have been reported for other Brazilian states ( Botelho-Souza et al, 2021 ; dos Santos et al, 2021 ). Lineage B.1 was predominant worldwide, especially in Europe, and emerged around January 2020 ( Rambaut et al, 2020 ), contributing to the early viral epidemic dynamics in Brazil ( Candido et al, 2020 ).…”
Section: Discussionsupporting
confidence: 74%
“…This study showed that 54% of the 22 participating families were male and 46% were female, with a proximal profile of uniformity in the parameters of gender differentiation, which is reported by the World Health Organization (WHO) worldwide [24]. Studies report that there is a verification of the profile of higher incidence in regions that have higher population density [24,25], which was verified in the study where the highest number of infected families is found in the city of Porto Velho, capital of the state of Rondônia, which has approximately 548,952 inhabitants and that since the beginning of the pandemic showed high rates of infection compared to other municipalities in the state [26,27].…”
Section: Discussionmentioning
confidence: 81%
“…The epidemiological data of COVID-19 in the State registers more than 13,700 deaths, and more than 950 thousand cases of the disease 11 . Nevertheless, exploratory and evolutionary studies were only conducted in some States of the country, such as Minas Gerais - MG 12 , Rondonia - RO 13 and Pernambuco - PE 14 . Therefore, taken into account this bottleneck of reported information, this study aimed at understanding the epidemiological dynamics of the virus in ES State, as well as its possible routes of transmission and dissemination.…”
Section: Introductionmentioning
confidence: 99%